Fit
By using a bonding film made of a conductive slurry containing metal particles, the heating and sintering mechanism of the conductive bonding layer and the adhesive layer is used to solve the problems of heat resistance and process complexity when bonding semiconductor elements and substrates, and the bonding of high heat resistance and high reliability is achieved.
Patent Information
- Application Number
- CN202111184223.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2016-11-18
- Filing Date
- 2017-11-09
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2037-11-09
AI Technical Summary
In the prior art, when bonding semiconductor elements with substrates, the connection heat resistance is insufficient, and the process is complicated, making it difficult to achieve high reliability bonding.
A bonding film made of a conductive slurry containing metal fine particles has a conductive bonding layer and an adhesive layer. The conductive bonding layer sinters metal particles by heating, and the adhesive layer is thermally decomposed during heating, thereby realizing mechanical bonding between the semiconductor element and the substrate.
The bonding of semiconductor elements with high heat resistance and high reliability with the substrate is achieved, and the bonding process is simplified, and the pollution problems caused by the use of flux are avoided.
Smart Images

Figure CN113921448B_ABST
Abstract
Description
[0001] The present application is a divisional application of an application filed on November 9, 2017, with application number 201780057303.9 and invention name “Bonding film, wafer processing tape, method for manufacturing a bonded body, and bonded body”. Technical Field
[0002] The present invention relates to a bonding film and a wafer processing tape, and in particular to a bonding film for bonding a semiconductor element to a substrate such as a circuit substrate or a ceramic substrate, and a wafer processing tape having the bonding film. Background Art
[0003] In the past, a film adhesive (die bonding film) was used to bond a semiconductor chip to a wiring substrate, etc. In addition, a dicing / die bonding tape has been developed, which has two functions: a dicing tape for fixing a semiconductor wafer when the semiconductor wafer is cut and separated (diced) into individual chips, and a die bonding film (also called a die bonding film) for bonding the cut semiconductor chip to a wiring substrate, etc. (see, for example, Patent Document 1).
[0004] When such dicing die bonding tape is used to connect a semiconductor element that controls and supplies electric power (so-called power semiconductor element) to a substrate such as a circuit board, a ceramic substrate, or a lead frame, there is a problem that the heat resistance of the connection is insufficient.
[0005] Therefore, solder is generally used in the connection between power semiconductor elements and substrates. As such solder, a paste solder having a suitable viscosity is mainly prepared by adding flux to the solder powder. However, if flux is used, the surface of the semiconductor element may be contaminated, and there is a problem of requiring a cleaning process. In addition, in recent years, for environmental reasons, it is required to use lead-free solder materials that do not contain lead. As a lead-free solder material that can cope with the heat generation of power semiconductors, there is Au-Sn solder, but due to its high price, it is not practical. As a solder material that is cheaper than Au-Sn solder, there is Sn-Ag-Cu solder, but there is a problem of reduced reliability due to the growth of intermetallic compounds caused by thermal history.
[0006] As a bonding member that does not use solder, there is an anisotropic conductive film (ACF) formed by mixing a material with conductive fine metal particles into a thermosetting resin in a film shape. However, since ACF contains a certain proportion of resin to obtain a good bonding state, the contact between the metal particles becomes point contact, and sufficient heat conduction cannot be expected, and there is a problem of insufficient heat resistance of the connection. In addition, since ACF may cause degradation of the thermosetting resin due to high heat, it is not suitable for connecting power semiconductors with high heat generation.
[0007] In addition, as another bonding member that does not use solder, there is a slurry containing metal particles (hereinafter referred to as metal slurry) (see, for example, Patent Document 2). Metal slurry is a material made by adding an organic dispersant to metal particles to prevent coagulation between metal particles during storage and in the manufacturing process, and a dispersion auxiliary substance that reacts with the organic dispersant during bonding to remove the organic dispersant, and mixing a solvent therein to form a slurry. The metal particles contain at least extremely fine particles with a particle size of about 1nm to 500nm, and the surface is in an active state.
[0008] When a semiconductor element is bonded to a substrate using metal paste, the metal paste is applied to the bonding surface of the semiconductor element and / or substrate using an applicator or screen printing, and heated at 150°C to 300°C for a given time (about 1 minute to 1 hour). As a result, the organic dispersant is removed by reaction with the dispersion auxiliary material, and the solvent is also removed by volatilization. When the organic dispersant and solvent are removed, the metal particles in the active state are bonded to each other to form a monomer film of the metal component.
[0009] When the metal paste is applied to the bonding surface using an applicator or screen printing, it is necessary to adjust the amount of solvent, etc. to reduce the viscosity of the metal paste to a certain extent. However, if the viscosity is reduced, when the metal paste is applied to the bonding surface, there is a problem that the metal paste splashes and adheres to the semiconductor element or the portion other than the bonding surface of the substrate, thereby contaminating the semiconductor element or the substrate.
[0010] Therefore, it has been proposed to prepare a sheet-shaped connection sheet using metal paste in advance (see Patent Document 3).
[0011] Existing patent literature
[0012] Patent Literature
[0013] Patent Document 1: Japanese Patent Application Publication No. 2010-265453
[0014] Patent Document 2: Japanese Patent Application Publication No. 2006-352080
[0015] Patent Document 3: Japanese Patent Application Publication No. 2013-236090 Summary of the invention
[0016] Problems to be solved by the invention
[0017] However, when a semiconductor element is bonded to a substrate using a connection sheet having a bonding layer formed in advance of a metal paste in a sheet shape as described in Patent Document 3, since the bonding layer itself does not have adhesiveness, it is necessary to place the bonding layer on the substrate using an adsorption fixture, place the semiconductor element thereon, and sinter the bonding layer. Therefore, there is a problem that the process becomes complicated.
[0018] Therefore, an object of the present invention is to provide a bonding film and a wafer processing tape which have sufficient heat resistance and high reliability for bonding a semiconductor element and a substrate and which simplify the bonding process.
[0019] Methods used to solve problems
[0020] In order to solve the above problems, the bonding film of the present invention is characterized in that it is a bonding film for bonding a semiconductor element to a substrate, having a conductive bonding layer obtained by forming a conductive paste containing metal particles (P) into a film shape, and a viscous layer having viscosity and stacked on the conductive bonding layer.
[0021] In order to solve the above problems, the bonding film of the present invention is characterized in that it is a bonding film for bonding a semiconductor element to a substrate, comprising a conductive bonding layer obtained by forming a conductive paste containing metal particles (P) into a film shape, and a sticky layer having stickiness and stacked on the conductive bonding layer, the sticky layer is thermally decomposed due to heating during bonding, and the metal particles (P) in the conductive bonding layer are sintered, thereby bonding the semiconductor element to the substrate.
[0022] Furthermore, it is preferred that the metal fine particles of the bonding film have an average primary particle size of 10 to 500 nm, and the conductive paste contains an organic solvent (S).
[0023] Furthermore, it is preferable that the metal fine particles (P) of the bonding film are composed of copper or silver.
[0024] Furthermore, it is preferred that the conductive paste of the bonding film contain an organic binder (R).
[0025] Furthermore, the adhesive layer of the bonding film preferably contains one or more selected from polyglycerol, glycerol fatty acid ester, polyglycerol fatty acid ester, phosphines, phosphites, sulfides, disulfides, trisulfides, and sulfoxides.
[0026] Furthermore, it is preferred that the organic solvent (S) of the bonding film contains an organic solvent (SC) having a boiling point of 100° C. or higher at normal pressure and composed of an alcohol and / or a polyol having one or more hydroxyl groups in the molecule.
[0027] In addition, it is preferred that the organic binder (R) of the above-mentioned bonding film is one or more selected from cellulose resin-based binders, acetate resin-based binders, acrylic resin-based binders, urethane resin-based binders, polyvinyl pyrrolidone resin-based binders, polyamide resin-based binders, butyral resin-based binders, and terpene-based binders.
[0028] In addition, in order to solve the above problems, the semiconductor processing tape of the present invention is characterized in that it has an adhesive film having a base film and an adhesive layer provided on the base film, and the above-mentioned bonding film, and a conductive bonding layer of the bonding film is provided on the adhesive layer.
[0029] In addition, in order to solve the above problems, the manufacturing method of the joint body of the present invention is characterized in that it has a joining step, wherein a joining film is arranged between a semiconductor element and a substrate and heated, the joining film having a conductive joining layer obtained by forming a conductive paste containing metal particles (P) into a film shape, and a sticky layer having stickiness and stacked on the conductive joining layer, the sticky layer is thermally decomposed to sinter the metal particles (P) of the conductive joining layer, thereby joining the semiconductor element to the substrate.
[0030] In addition, in order to solve the above problems, the semiconductor and substrate joint body of the present invention is characterized in that it is a semiconductor and substrate joint body having a conductive connecting component composed of a metal porous body on the substrate and a semiconductor element thereon, and the porosity of the metal porous body is 6 to 9%, and the average pore diameter is 15 to 120 nm.
[0031] Effects of the Invention
[0032] According to the present invention, it is possible to provide a bonding film, a wafer processing tape, a method for producing a bonded product, and a bonded product, which have sufficient heat resistance and high reliability and can facilitate a bonding step for bonding a semiconductor element to a substrate. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a cross-sectional view schematically showing the wafer processing tape according to the embodiment of the present invention.
[0034] Figure 2 This is a picture showing a semiconductor wafer attached to a wafer processing tape.
[0035] Figure 3 This is a diagram for explaining the cutting process.
[0036] Figure 4 It is a diagram for explaining the expansion process.
[0037] Figure 5 It is a figure for explaining the picking-up process.
[0038] Figure 6 It is a cross-sectional view schematically showing a semiconductor device manufactured using the wafer processing tape according to the embodiment of the present invention. DETAILED DESCRIPTION
[0039] Hereinafter, an adhesive film and a wafer processing tape according to embodiments of the present invention will be described with reference to the accompanying drawings. Figures 1 to 5 A wafer processing tape according to one embodiment of the present invention will be described. Figure 1 It is a cross-sectional view showing a wafer processing tape 10 according to one embodiment. Figure 2 1 is a diagram showing a state where a semiconductor wafer 1 is attached to a wafer processing tape 10. Figure 3 is a diagram for explaining a dicing step in a semiconductor device manufacturing process. Figure 4 is a diagram for explaining the expansion process. Figure 5 It is a figure for explaining the picking-up process. Figure 6 It is a cross-sectional view schematically showing a semiconductor device manufactured using the wafer processing tape according to the embodiment of the present invention.
[0040] like Figure 1 As shown, a wafer processing tape 10 according to an embodiment of the present invention comprises: an adhesive film 12 including a base film 12a and an adhesive layer 12b formed thereon, and a bonding film 13 laminated on the adhesive film 12. The bonding film 13 comprises a conductive bonding layer 13a obtained by forming a conductive paste containing metal particles (P) into a film shape, and an adhesive layer 13b having adhesiveness and laminated on the conductive bonding layer 13a, and the conductive bonding layer 13a is provided on the adhesive layer 12b. The wafer processing tape 10 is used in a dicing process of cutting a semiconductor wafer 1 into semiconductor elements 2 (also referred to as chips or semiconductor chips), and in bonding the cut semiconductor elements 2 to a substrate 40 such as a circuit board, a ceramic substrate, and a lead frame (see Figure 6 ) chip bonding process. For the dicing process, refer to Figure 3 This will be described later.
[0041] It should be noted that the adhesive layer 12b may be composed of a single adhesive layer or may be composed of an adhesive layer in which two or more adhesive layers are stacked. Figure 1 , a release film 11 is provided on the wafer processing tape 10 in order to protect the bonding film 13. As the release film 11, a known release film can be used.
[0042] The adhesive film 12 and the bonding film 13 can be formed in advance into a predetermined shape in accordance with the use process and equipment.
[0043] Hereinafter, each component of the wafer processing tape 10 according to the present embodiment will be described in detail.
[0044] (Jointing film)
[0045] After the bonding film 13 is bonded to the semiconductor wafer 1 and diced, when picking up the singulated semiconductor element 2, it is peeled off from the adhesive film 12 and picked up while being attached to the semiconductor element 2, and is used as a bonding material when fixing the semiconductor element 2 to the substrate 40. Therefore, in the picking-up process, the bonding film 13 has adhesiveness and peelability that allows it to be peeled off from the adhesive film 12 while still attached to the singulated semiconductor element 2, and furthermore, the semiconductor element 2 and the substrate 40 are bonded with sufficient bonding reliability. For the picking-up process, refer to Figure 5 This will be described later.
[0046] The bonding film 13 includes a conductive bonding layer 13 a formed by forming a conductive paste containing metal fine particles (P) into a film shape, and an adhesive layer 13 b having adhesiveness and laminated on the conductive bonding layer 13 a .
[0047] It should be noted that the tackiness in the present invention refers to adhesiveness, and specifically refers to adhesiveness that can hold the semiconductor wafer 1 and the semiconductor element 2 with the conductive bonding layer 13 a .
[0048] [Conductive bonding layer]
[0049] The conductive paste preferably contains an organic dispersion medium (D) in addition to the metal fine particles (P).
[0050] As the metal particles (P) contained in the conductive paste, there can be used one kind of particles selected from the group of metal elements consisting of copper, magnesium, aluminum, zinc, gallium, indium, tin, antimony, lead, bismuth, titanium, manganese, germanium, silver, gold, nickel, platinum and palladium; particles obtained by mixing two or more kinds of particles selected from the group of metal elements; particles of an alloy containing two or more elements selected from the group of metal elements; particles obtained by mixing one kind of particles selected from the group of metal elements or particles obtained by mixing two or more kinds of particles selected from the group of metal elements with particles of an alloy containing two or more elements selected from the group of metal elements, their oxides, or their hydroxides, etc.
[0051] Considering the conductivity and the sintering property during the heat treatment, the metal particles (P) preferably use (i) copper particles (P1), or (ii) metal particles composed of 90-100% by mass of copper particles (P1) and 10-0% by mass of second metal particles (P2) selected from one or more of magnesium, aluminum, zinc, gallium, indium, tin, antimony, lead, bismuth, titanium, manganese, and germanium. The copper particles (P1) are metals with relatively high conductivity, while the metal particles (P2) are metals with relatively low melting points. When the second metal particles (P2) are used in the copper particles (P1), it is preferred that the metal particles (P2) form an alloy with the copper particles (P1) in the metal particles (P), or the metal particles (P2) form a coating layer on the surface of the copper particles (P1) in the metal particles (P). By using the copper particles (P1) and the metal particles (P2) in combination, the heat treatment temperature can be lowered, or the bonding between the metal particles can be made easier.
[0052] The average primary particle size of the metal particles (P) before the heat treatment is preferably 10 to 500 nm. If the average particle size of the metal particles (P) is less than 10 nm, it may be difficult to form uniform particle size and pores throughout the entire sintered body by heat treatment (sintering), and the thermal cycle characteristics are reduced, and the bonding strength is also reduced. On the other hand, if the average particle size is greater than 500 nm, the diameter of the metal particles and pores constituting the sintered body is close to the micron size, and the thermal cycle characteristics are still reduced. For the average particle size of the metal particles (P) before the heat treatment, the diameter can be measured using a scanning electron microscope (SEM). For example, in the case of a two-dimensional shape that is approximately circular, the diameter of the circle is measured, in the case of an approximately elliptical shape, the short diameter of the ellipse is measured, in the case of an approximately square shape, the length of the side of the square is measured, and in the case of an approximately rectangular shape, the length of the short side of the rectangle is measured. The "average particle size" is obtained by observing and measuring the particle sizes of a plurality of particles randomly selected from 10 to 20 using the above-mentioned microscope, and calculating the average value.
[0053] The method for producing the metal fine particles (P) is not particularly limited, and for example, a wet chemical reduction method, an atomization method, a plating method, a plasma CVD method, an MOCVD method, or the like can be used.
[0054] The method for producing metal particles (P) having an average primary particle size of 10 to 500 nm can specifically be the method disclosed in Japanese Patent Application Publication No. 2008-231564. If the production method disclosed in the publication is adopted, metal particles (P) having an average primary particle size of 10 to 500 nm can be easily obtained. In addition, in the method for producing metal particles disclosed in the publication, a coagulant can be added to the reduction reaction aqueous solution after the reduction reaction of the metal ions is completed, and an organic dispersion medium (D) can be added to the metal particles recovered by centrifugal separation and the impurities in the reaction solution are removed, and kneaded to produce the conductive paste of the present invention.
[0055] In order to uniformly disperse the metal particles (P) in the conductive paste, it is important to select a specific organic dispersion medium (D) that is excellent in dispersibility and sintering properties during heat treatment. The organic dispersion medium (D) disperses the metal particles (P) in the conductive paste, adjusts the viscosity of the conductive paste, maintains the film shape, and can function as a reducing agent in liquid and gaseous states during heat treatment. The organic dispersion medium (D) contains at least an organic solvent (S), and preferably also contains an organic binder (R).
[0056] The organic solvent (S) preferably contains an organic solvent (SC) having a boiling point of 100° C. or more at normal pressure and composed of an alcohol and / or polyol having one or more hydroxyl groups in the molecule. In addition, the organic solvent (S) is preferably selected from (i) an organic solvent (S1) and (ii) an organic solvent (S2), wherein the organic solvent (S1) contains at least 5 to 90% by volume of an organic solvent (SA) having an amide group, 5 to 45% by volume of a low-boiling organic solvent (SB) having a boiling point of 20 to 100° C. at normal pressure, and 5 to 90% by volume of an organic solvent (SC) having a boiling point of 100° C. or more at normal pressure and composed of an alcohol and / or polyol having one or more hydroxyl groups in the molecule, and the organic solvent (S2) contains at least 5 to 95% by volume of an organic solvent (SA) having an amide group and 5 to 95% by volume of an organic solvent (SC) having a boiling point of 100° C. or more at normal pressure and composed of an alcohol and / or polyol having one or more hydroxyl groups in the molecule.
[0057] When other organic solvent components than those mentioned above are added, polar organic solvents such as tetrahydrofuran, diglyme, ethylene carbonate, propylene carbonate, sulfolane, and dimethyl sulfoxide can be used.
[0058] The organic solvent (S1) is an organic solvent containing at least 5 to 90% by volume of an organic solvent (SA) having an amide group, 5 to 45% by volume of a low-boiling point organic solvent (SB) having a boiling point of 20 to 100° C. at normal pressure, and 5 to 90% by volume of an organic solvent (SC) having a boiling point of 100° C. or more at normal pressure and composed of an alcohol and / or polyol having one or more hydroxyl groups in the molecule. The organic solvent (SA) is contained in the organic solvent (S1) at 5 to 90% by volume, and has the effect of improving the dispersibility and storage stability in the conductive paste, and also improving the adhesion at the bonding surface when the conductive bonding layer on the bonding surface is subjected to a heat treatment to form a sintered body. The organic solvent (SB) is contained in the organic solvent (S1) at 5 to 45% by volume or more, and has the effect of reducing the interaction between solvent molecules in the conductive paste and improving the affinity between the dispersed metal particles (P) and the organic solvent (S1). The organic solvent (SC) is contained in the organic solvent (S1) in an amount of 5 to 90% by volume, which can achieve dispersibility in the conductive paste and further long-term stabilization of the dispersibility. In addition, if the organic solvent (SC) is present in the mixed organic solvent, when the conductive bonding layer is arranged on the bonding surface and heat-treated, the uniformity of the sintered body is improved, and the reduction-promoting effect of the oxide film of the organic solvent (SC) is also exerted, so that a highly conductive bonding member can be obtained. The so-called "organic solvent (S1) is an organic solvent containing at least 5 to 90 volume % of an organic solvent (SA), 5 to 45 volume % of an organic solvent (SB), and 5 to 90 volume % of an organic solvent (SC)." means that the organic solvent (S1) can be blended from an organic solvent (SA), an organic solvent (SB), and an organic solvent (SC) in the above-mentioned blending ratio to reach 100 volume %, and other organic solvent components can also be blended within the range of the above-mentioned blending ratio and within the range that does not impair the effect of the present invention. In this case, it is preferred that the component composed of the organic solvent (SA), the organic solvent (SB), and the organic solvent (SC) is contained in 90 volume % or more, and more preferably contains 95 volume % or more.
[0059] The organic solvent (S2) is an organic solvent containing at least 5 to 95% by volume of an organic solvent (SA) having an amide group, and 5 to 95% by volume of an organic solvent (SC) having a boiling point of 100°C or more at normal pressure and composed of an alcohol and / or polyol having 1 or more hydroxyl groups in the molecule. The organic solvent (SA) is contained in the organic solvent (S2) at 5 to 95% by volume, and has the effect of improving dispersibility and storage stability in the mixed organic solvent, and also improving the adhesion at the bonding surface when the conductive paste is heated to form a metal porous body. The organic solvent (SC) is contained in the organic solvent (S2) at 5 to 95% by volume, and further improves dispersibility in the conductive paste. In addition, if the organic solvent (SA) and the organic solvent (SC) are present in the organic solvent (S2), when the conductive bonding layer is arranged on the bonding surface and then heated, sintering can be promoted even at a relatively low heating treatment temperature. The so-called "organic solvent (S2) is an organic solvent containing at least 5 to 95 volume % of an organic solvent (SA) and 5 to 95 volume % of an organic solvent (SC)." means that the organic solvent (S2) can be blended from the organic solvent (SA) and the organic solvent (SC) in the above-mentioned blending ratio to reach 100 volume %, and other organic solvent components can also be blended within the range of the above-mentioned blending ratio and within the range that does not impair the effect of the present invention. In this case, it is preferred that the component composed of the organic solvent (SA) and the organic solvent (SC) is contained in an amount of 90 volume % or more, and more preferably contains 95 volume % or more.
[0060] Specific examples of the above-mentioned organic solvent (SC), organic solvent (SA), and organic solvent (SB) are shown below.
[0061] The organic solvent (SC) is an organic compound having a boiling point of 100°C or more at normal pressure, and composed of alcohols and / or polyols having 1 or more hydroxyl groups in the molecule and having reducing properties. In addition, alcohols having 5 or more carbon atoms and polyols having 2 or more carbon atoms are preferred, and organic solvents that are liquid at room temperature and have a high relative dielectric constant, such as organic solvents having 10 or more carbon atoms, are preferred. Metal particles (P) having an average primary particle size of 10 to 500 nm have a large surface area of the particles, so the influence of oxidation needs to be considered. However, the organic solvent (SC) listed below functions as a reducing agent in liquid and gaseous form during heat treatment (sintering), so it inhibits the oxidation of the metal particles (P) during heat treatment and promotes sintering. Specific examples of the organic solvent (SC) include ethylene glycol, diethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 2-butene-1,4-diol, 2,3-butylene glycol, pentanediol, hexanediol, octanediol, glycerol, 1,1,1-trihydroxymethylethane, 2-ethyl-2-hydroxymethyl-1,3-propylene glycol, 1,2,6-hexanetriol, 1,2,3-hexanetriol, and 1,2,4-butanetriol.
[0062] In addition, as specific examples of the organic solvent (SC), sugar alcohols such as threitol (D-Threitol), erythritol (Erythritol), pentaerythritol (Pentaerythritol), pentitol (Pentitol), and hexitol (Hexitol) can also be used. Among the pentitols, xylitol (Xylitol), ribitol (Ribitol), and arabitol (Arabitol) are included. Among the hexitols, mannitol (Mannitol), sorbitol (Sorbitol), and dulcitol (Dulcitol) are included. In addition, glyceraldehyde (Glyceraldehyde) can also be used. aldehyde), dihydroxyacetone, threose, erythrulose, erythrose, arabinose, ribose, ribulose, xylose, xylulose, lyxose, glucose, fructose, mannose, idose, sorbose, gulose Sugars such as galactose, talose, tagatose, galactose, allose, altrose, lactose, isomaltose, glucoheptose, heptose, maltotriose, lactulose, trehalose, etc., but sugars with high melting points can be mixed with other organic solvents (SC) with low melting points. Among the above alcohols, polyols having two or more hydroxyl groups in the molecule are more preferred, and ethylene glycol and glycerol are particularly preferred.
[0063] The organic solvent (SA) is a compound having an amide group (-CONH-), and a compound having a high relative dielectric constant is particularly preferred. Examples of the organic solvent (A) include N-methylacetamide (191.3 at 32°C), N-methylformamide (182.4 at 20°C), N-methylpropionamide (172.2 at 25°C), formamide (111.0 at 20°C), N,N-dimethylacetamide (37.78 at 25°C), 1,3-dimethyl-2-imidazolidinone (37.6 at 25°C), N,N-dimethylformamide (36.7 at 25°C), 1-methyl-2-pyrrolidone (32.58 at 25°C), hexamethylphosphoric acid triamide (29.0 at 20°C), 2-pyrrolidone, ε-caprolactam, acetamide, etc., and these may be used in combination. It should be noted that the numbers in parentheses after the names of the compounds having an amide group above represent the relative dielectric constants of the respective solvents at the measurement temperature. Among them, N-methylacetamide, N-methylformamide, formamide, acetamide, etc. having a relative dielectric constant of 100 or more can be suitably used. In the case of a solid at room temperature such as N-methylacetamide (melting point: 26-28° C.), it can be mixed with other solvents and used as a liquid at the processing temperature.
[0064] The organic solvent (SB) is an organic compound having a boiling point in the range of 20 to 100°C at normal pressure. If the boiling point at normal pressure is lower than 20°C, when the particle dispersion containing the organic solvent (SB) is stored at room temperature, the components of the organic solvent (SB) will volatilize and the slurry composition may change. In addition, when the boiling point at normal pressure is lower than 100°C, the mutual attraction between the solvent molecules caused by the addition of the solvent is reduced, and it can be expected that the effect of further improving the dispersibility of the particles can be effectively exerted. As the organic solvent (SB), the general formula R 1 -OR 2 (R 1 , R 2 Each independently represents an alkyl group having 1 to 4 carbon atoms. 3 -OH(R 3 is an alkyl group having 1 to 4 carbon atoms. 4 -C(=O)-R 5 (R 4 , R 5 Each independently represents an alkyl group having 1 to 2 carbon atoms. A ketone compound (SB3) represented by the general formula R 6 -(NR 7 )-R 8 (R 6 , R 7 , R 8Each independently represents an alkyl group or a hydrogen atom and has 0 to 2 carbon atoms. An amine compound (SB4) represented by
[0065] The organic solvents (SB) are exemplified below. The numbers in parentheses after the compound names indicate boiling points at normal pressure. Examples of the ether compounds (SB1) include diethyl ether (35°C), methyl propyl ether (31°C), dipropyl ether (89°C), diisopropyl ether (68°C), methyl tert-butyl ether (55.3°C), tert-amyl methyl ether (85°C), divinyl ether (28.5°C), ethyl vinyl ether (36°C), and allyl ether (94°C). Examples of the alcohols (SB2) include methanol (64.7°C), ethanol (78.0°C), 1-propanol (97.15°C), 2-propanol (82.4°C), 2-butanol (100°C), and 2-methyl-2-propanol (83°C). Examples of the ketone compounds (SB3) include acetone (56.5°C), methyl ethyl ketone (79.5°C), and diethyl ketone (100°C). Examples of the amine compound (SB4) include triethylamine (89.7° C.) and diethylamine (55.5° C.).
[0066] The organic binder (R) has the functions of inhibiting the aggregation of metal particles (P) in the conductive paste, adjusting the viscosity of the conductive paste, and maintaining the shape of the conductive connection member precursor. The organic binder (R) is preferably selected from one or more of a cellulose resin binder, an acetate resin binder, an acrylic resin binder, a urethane resin binder, a polyvinyl pyrrolidone resin binder, a polyamide resin binder, a butyral resin binder, and a terpene binder. Specifically, it is preferably selected from one or more of the following substances, that is, the cellulose resin binder is acetyl cellulose, methyl cellulose, ethyl cellulose, butyl cellulose, and nitrocellulose; the acetate resin binder is methyl glycol acetate, ethyl glycol acetate, butyl glycol acetate, ethyl diglycol acetate, and butyl diglycol acetate; the acrylic resin binder is methyl methacrylate, ethyl methacrylate, and butyl methacrylate; the urethane resin binder is 2,4-toluene diisocyanate and p-phenylene diisocyanate; the polyvinyl pyrrolidone resin binder is polyvinyl pyrrolidone and N-vinyl pyrrolidone; the polyamide resin binder is polyamide 6, polyamide 66, and polyamide 11; the butyral resin binder is polyvinyl butyral; the terpene binder is pinene, eucalyptol, limonene, and terpineol.
[0067] Conductive paste is a conductive paste containing metal particles (P) and an organic dispersion medium (D) containing an organic solvent (S), or a conductive paste containing the metal particles (P) and an organic dispersion medium (D) containing an organic solvent (S) and an organic binder (R). If it is subjected to heat treatment, when a certain temperature is reached, the evaporation of the organic solvent (S) or the evaporation of the organic solvent (S) and the thermal decomposition of the organic binder (R) are promoted, and the surface of the metal particles (P) is revealed, and the principle of bonding (sintering) to each other at the surface is utilized to act as a bonding material. The mixing ratio (P / D) of the metal particles (P) and the organic dispersion medium (D) in the conductive paste is preferably 50 to 85 mass% / 50 to 15 mass% (the total mass% is 100 mass%). It should be noted that metal particles, organic dispersion media, etc. other than the above can be mixed into the conductive paste of the present invention within the range that does not impair the effect of the present invention.
[0068] If the proportion of the metal particles (P) is greater than 85% by mass, the slurry becomes highly viscous, and insufficient bonding between the surfaces of the metal particles (P) may occur during the heating process, thereby reducing the conductivity. On the other hand, if the proportion of the metal particles (P) is less than 50% by mass, the viscosity of the slurry is reduced and it is difficult to maintain the film shape. In addition, it is possible that shrinkage may occur during the heating process. In addition, there may be an unfavorable situation in which the rate of evaporation of the organic dispersion medium (D) slows down during the heating process. From this point of view, the proportion (P / D) of the metal particles (P) and the organic dispersion medium (D) is more preferably 55-80% by mass / 45-20% by mass. In addition, the proportion (S / R) of the organic solvent (S) and the organic binder (R) in the organic dispersion medium (D) is preferably 80-100% by mass / 20-0% by mass (the total of the mass % is 100% by mass).
[0069] If the proportion of the organic binder (R) in the organic dispersion medium (D) is greater than 20% by mass, the speed at which the organic binder (R) is thermally decomposed and scattered slows down when the conductive bonding layer 13a is heat-treated. In addition, when the amount of residual carbon in the conductive connecting member increases, sintering is hindered, and problems such as cracks and peeling may occur, so it is not preferred. Depending on the choice of the organic solvent (S), in the case where the metal particles (P) can be evenly dispersed using only the solvent, the viscosity of the conductive paste can be adjusted, and the shape of the film can be maintained, a component containing only an organic solvent (S) can be used as an organic dispersion medium (D). In the conductive paste, known additives such as a defoamer, a dispersant, a plasticizer, a surfactant, and a thickener can be added to the components as needed. When manufacturing the conductive paste, a ball mill or the like can be used to mix the components.
[0070] [Sticky layer]
[0071] The adhesive layer 13b is a layer for holding the semiconductor wafer 1 and the semiconductor element 2 on the conductive bonding layer 13a, and has adhesiveness. In addition, the adhesive layer 13b is thermally decomposed by heating when the semiconductor element 2 is bonded to the substrate 40. The adhesive layer 13b is not particularly limited as long as it is a layer having such properties, and can be made of any material.
[0072] Since the conductive bonding layer 13a has no stickiness, the adhesive layer 13b is a layer for improving the adhesion between the semiconductor wafer 1, the semiconductor element 2 and the conductive bonding layer 13a. Without the adhesive layer 13b, the adhesion between the semiconductor wafer 1, the semiconductor element 2 and the conductive bonding layer 13a is weak, so when the semiconductor wafer 1 is cut or the semiconductor element 2 is picked up, peeling will occur between the semiconductor wafer 1, the semiconductor element 2 and the conductive bonding layer 13a. In addition, the adhesive layer 13b is also a layer for improving the adhesion between the conductive bonding layer 13a and the semiconductor wafer 1 and the semiconductor element 2. By improving the adhesion, the bonding strength when the semiconductor element 2 is bonded to the substrate 40 through the conductive bonding layer 13a is also improved.
[0073] In the present invention, it is important that the adhesive layer 13b is thermally decomposed by heating when the semiconductor element 2 is bonded to the substrate 40, thereby mechanically bonding the semiconductor element 2 to the substrate 40 via the conductive bonding layer 13a. For this reason, the weight loss of the adhesive layer 13b in a thermogravimetric measurement at a heating temperature during bonding, in an air atmosphere, and at a heating rate of 5°C / min is preferably 70% by weight or more, more preferably 85% by weight or more, and even more preferably 95% by weight or more.
[0074] In addition, since the adhesive layer 13b is in direct contact with the semiconductor element 2 during bonding, it is also expected that the surface of the electrode of the semiconductor element 2 can be activated. This is considered to be because the substance contained in the adhesive layer 13b reacts with the oxide layer on the surface of the metal electrode when it is decomposed during heating, thereby cleaning the metal surface. By activating the surface of the electrode of the semiconductor element 2 in this way, the adhesion between the electrode of the semiconductor element 2 and the conductive bonding layer 13a can be improved.
[0075] As the material constituting the viscous layer 13b, it is preferable to use a material that is insoluble in polar or non-polar solvents at room temperature, but easily soluble in polar or non-polar solvents when heated to a melting point. After heating such a material to a melting point and dissolving in a solvent, coating the conductive bonding layer 13a, etc., cooling to room temperature to evaporate the solvent, a film-like body having viscosity can be formed. As the solvent, a known solvent can be used appropriately, but in order to facilitate evaporation during film formation, a solvent with a low boiling point is preferably used.
[0076] In addition, the viscous layer 13b is more preferably composed of a substance that reduces the metal particles (P) when the metal particles (P) in the conductive paste are heated and sintered. If the substance causes the decomposition reaction of the viscous layer 13b in a multi-stage reaction, the reaction temperature range is wide, and the metal particles (P) are reduced, thereby reducing the resistivity of the metal particles (P) after sintering and improving the conductivity.
[0077] The adhesive layer 13b preferably contains, for example, polyglycerol; glycerol fatty acid esters such as glycerol monocaprate (melting point: 46°C), glycerol monolaurate (melting point: 57°C), glycerol monostearate (melting point: 70°C), and glycerol monobehenate (melting point: 85°C); fatty acid polyglycerol esters such as diglycerol stearate (melting point: 61°C) and diglycerol laurate (melting point: 34°C); styrene-p-styrene diphenylphosphine (melting point: 75°C), triphenylphosphine (melting point: 8 1°C), tri-n-octylphosphine (melting point: 30°C), etc. phosphines; phosphites; sulfides such as bis(4-methacryloylthiophenyl) sulfide (melting point: 64°C), phenyl-p-tolyl sulfide (melting point: 23°C), furfuryl sulfide (melting point: 32°C), etc.; disulfides such as diphenyl disulfide (melting point: 61°C), benzyl disulfide (melting point: 72°C), tetraethylthiuram disulfide (melting point: 70°C), etc.; trisulfides; and one or more of sulfoxides.
[0078] In addition, the viscous layer 13b can be added with known additives such as defoaming agents, dispersants, plasticizers, surfactants, thickeners, etc. as needed within a range that does not hinder viscosity and thermal decomposition and does not cause problems in contamination of the semiconductor element 2 and the substrate 40 and the generation of boiling gas.
[0079] Next, a method for manufacturing the bonding film 13 is described. First, a release film is placed on a loading table, and a spacer is arranged on the release film. The spacer is, for example, a plate made of a metal such as SUS, and has a circular opening in the center. The above-mentioned conductive paste is arranged in the opening of the spacer and on the release film, and a scraper is used to perform screen printing and uniformly roll the conductive paste, thereby making the conductive paste into a circular film shape. Thereafter, the release film and the spacer are removed. Then, the conductive paste formed into a circular film shape is pre-dried to form a conductive bonding layer 13a. The pre-drying time depends on the printing thickness, for example, it can be set to 5 to 20 minutes.
[0080] Then, the materials constituting the above-mentioned adhesive layer 13b are heated and kneaded in a solvent, applied on the conductive bonding layer 13a by a doctor blade method or a spray method, and cooled. Then, the adhesive layer 13b is formed by heating and drying to evaporate the solvent.
[0081] It should be noted that, in the present embodiment, the bonding film 13 of the present invention is provided on the adhesive film 12, and constitutes the wafer processing tape 10 as a whole. However, the bonding film 13 may be used alone as a material for manufacturing the wafer processing tape 10. In this case, the bonding film 13 is preferably protected on both sides by a protective film. As the protective film, a polyethylene-based, polystyrene-based, polyethylene terephthalate (PET)-based film may be used. In addition, a known protective film such as a film subjected to a demolding treatment may be used. From the viewpoint of having a hardness suitable for maintaining the bonding film 13, a polyethylene film or a polystyrene film is preferably used. The thickness of the protective film is not particularly limited and may be appropriately set, but is preferably 10 to 300 μm.
[0082] (Adhesive film)
[0083] The adhesive film 12 has an adhesive force sufficient to prevent the semiconductor wafer 1 held by the bonding film 13 from peeling off when the semiconductor wafer 1 is cut, and has an adhesive force low enough to be easily peeled off from the bonding film 13 when picking up the singulated semiconductor element 2 after cutting. Figure 1 In the figure, an adhesive film in which an adhesive layer 12b is provided on a base film 12a is exemplified, but the present invention is not limited thereto, and a known adhesive film used as a dicing tape can be used.
[0084] The base film 12a of the adhesive film 12 can be used without particular limitation as long as it is a conventionally known base film. However, as described later, in this embodiment, a radiation-curable material among energy-curable materials is used as the adhesive layer 12b, and therefore a radiation-transmissive material is used.
[0085] For example, as the material of the substrate film 12a, homopolymers or copolymers of α-olefins such as polyethylene, polypropylene, ethylene-propylene copolymer, polybutene-1, poly-4-methylpentene-1, ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, ethylene-methyl acrylate copolymer, ethylene-acrylic acid copolymer, ionomers, or mixtures thereof, thermoplastic elastomers such as polyurethane, styrene-ethylene-butene copolymer or pentene copolymer, polyamide-polyol copolymer, and mixtures thereof can be cited. In addition, the substrate film 12a can be a film obtained by mixing two or more materials selected from them, or a film in which they are monolayered or multilayered. The thickness of the substrate film 12a is not particularly limited and can be appropriately set, but is preferably 50 to 200 μm.
[0086] In this embodiment, the adhesive layer 12b is cured by irradiating the adhesive film 12 with radiation such as ultraviolet rays, and the adhesive layer 12b is easily peeled off from the bonding film 13. Therefore, as the resin of the adhesive layer 12b, it is preferred to prepare the adhesive by appropriately mixing radiation polymerizable compounds with various elastomers such as known chlorinated polypropylene resins, acrylic resins, polyester resins, polyurethane resins, epoxy resins, addition reaction type organic polysiloxane resins, silicone acrylate resins, ethylene-vinyl acetate copolymers, ethylene-ethyl acrylate copolymers, ethylene-methyl acrylate copolymers, ethylene-acrylic acid copolymers, polyisoprene or styrene / butadiene copolymers or their hydrides, or mixtures thereof. In addition, various surfactants and surface smoothing agents may also be added. The thickness of the adhesive layer 12b is not particularly limited and can be appropriately set, but is preferably 5 to 30 μm.
[0087] As the radiation polymerizable compound, for example, a low molecular weight compound having at least two photopolymerizable carbon-carbon double bonds in the molecule that can be three-dimensionally networked by light irradiation, a polymer or oligomer having a photopolymerizable carbon-carbon double bond group in a substituent, etc. can be used. Specifically, trimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, dipentaerythritol monohydroxy pentaacrylate, dipentaerythritol hexaacrylate, 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, polyethylene glycol diacrylate, oligoester acrylate, copolymers of acrylic acid or various acrylates such as silicone acrylate, etc. can be used.
[0088] In addition, in addition to the above-mentioned acrylate compounds, carbamate acrylate oligomers can also be used. Carbamate acrylate oligomers are obtained by the following operation, that is, polyester-type or polyether-type polyol compounds and polyisocyanate compounds (such as 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 1,3-xylene diisocyanate, 1,4-xylene diisocyanate, diphenylmethane 4,4-diisocyanate, etc.) are reacted to make acrylate or methacrylate with hydroxyl (such as 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, polyethylene glycol acrylate, polyethylene glycol methacrylate, etc.) react with the obtained terminal isocyanate carbamate prepolymer. It should be noted that as the adhesive layer 12b, it can also be an adhesive layer obtained by mixing two or more selected from the above-mentioned resins.
[0089] As the composition of the adhesive layer 12 b , a radiation-polymerizable compound that cures upon irradiation with radiation may be used, or a composition appropriately blended with an acrylic adhesive, a photopolymerization initiator, a curing agent, and the like may be used.
[0090] When a photopolymerization initiator is used, for example, benzoin isopropyl ether, benzoin isobutyl ether, benzophenone, Michler's ketone, chlorothioxanthone, dodecylthioxanthone, dimethylthioxanthone, diethylthioxanthone, benzyl dimethyl ketal, α-hydroxycyclohexyl phenyl ketone, 2-hydroxymethylphenyl propane, etc. The amount of these photopolymerization initiators to be added is preferably 0.01 to 5 parts by mass relative to 100 parts by mass of the acrylic copolymer.
[0091] The adhesive film 12 can be manufactured by a conventionally known method as a method for manufacturing a dicing tape. The wafer processing tape 10 can be manufactured by bonding the conductive bonding layer 13 a of the conductive bonding layer 13 described above to the adhesive layer 12 b of the adhesive film 12 .
[0092] (How to use wafer processing tape)
[0093] In the semiconductor device 100 (see Figure 6 ) in the manufacturing process, the wafer processing tape 10 is used as follows. Figure 2 , a state where a semiconductor wafer 1 and a die-bonding ring frame 20 are bonded to a wafer processing tape 10 is shown.
[0094] First, if Figure 2 As shown, the adhesive layer 12b of the adhesive film 12 is attached to the die ring frame 20, and the semiconductor wafer 1 is attached to the adhesive layer 13b of the bonding film 13. There is no limitation on the order of attaching them, and the adhesive layer 12b of the adhesive film 12 may be attached to the die ring frame 20 after the semiconductor wafer 1 is attached to the bonding film 13. In addition, the adhesive film 12 may be attached to the die ring frame 20 and the semiconductor wafer 1 may be attached to the bonding film 13 simultaneously.
[0095] Then, if Figure 3As shown, a dicing process of the semiconductor wafer 1 is performed, and then a process of irradiating the adhesive film 12 with energy rays, such as ultraviolet rays, is performed. Specifically, first, in order to cut the semiconductor wafer 1 and the bonding film 13 by the dicing blade 21, the wafer processing tape 10 is adsorbed and supported from the surface side of the adhesive film 12 by the adsorption stage 22. Then, the semiconductor wafer 1 and the bonding film 13 are cut into semiconductor element 2 units by the dicing blade 21 and singulated, and then the energy rays are irradiated from the lower surface side of the adhesive film 12. By irradiating the energy rays, the adhesive layer 12b is cured and its adhesive force is reduced. It should be noted that, instead of irradiating with energy rays, the adhesive force of the adhesive layer 12b of the adhesive film 12 can be reduced by external stimulation such as heating. In the case where the adhesive layer 12b is composed of two or more adhesive layers stacked, one or all of the adhesive layers can be cured by irradiating with energy rays, thereby reducing the adhesive force of one or all of the adhesive layers.
[0096] Afterwards, if Figure 4 As shown, an expansion process is performed to extend the adhesive film 12 holding the cut semiconductor elements 2 and the bonding film 13 in the circumferential direction of the die ring frame 20. Specifically, the hollow cylindrical push-up member 30 is raised from the lower surface side of the adhesive film 12 holding the cut semiconductor elements 2 and the bonding film 13, and the adhesive film 12 is extended in the circumferential direction of the die ring frame 20.
[0097] After the expansion process is implemented, Figure 5 As shown in FIG. 1 , the pick-up process of picking up the semiconductor element 2 is performed while the adhesive film 12 is kept expanded. Specifically, the semiconductor element 2 is pushed up from the lower surface side of the adhesive film 12 by the support rod 31, and the semiconductor element 2 is sucked from the upper surface side of the adhesive film 12 by the suction jig 32, thereby picking up the singulated semiconductor element 2 together with the bonding film 13.
[0098] Then, after the pick-up process is performed, the bonding process is performed. Specifically, the conductive bonding layer 13a side of the bonding film 13 picked up together with the semiconductor element 2 in the pick-up process is arranged at the bonding position of the substrate 40 such as the lead frame and the package substrate. Thereafter, the bonding film 13 is subjected to a heat treatment at a temperature of 150 to 350°C. At this time, the adhesive layer 13b is thermally decomposed, and the organic dispersion medium (D) in the conductive bonding layer 13a is removed, and the metal particles (P) are condensed at a temperature lower than the melting point of the metal in the bulk state due to their surface energy, and the bonding (sintering) between the surfaces of the metal particles is intensified, forming a conductive connection member 50 composed of a porous metal body. If an organic solvent (SC) is contained in the organic solvent (S) during the heat treatment, since the solvent exerts a reducing function in a liquid and gaseous state, the oxidation of the metal particles (P) is suppressed and sintering is promoted. It should be noted that, when the organic dispersion medium (D) in the conductive bonding layer 13a contains an organic solvent (S) with a low boiling point, a drying process can be pre-set before the heat treatment to evaporate and remove at least a portion of the organic solvent (S). By means of this heat treatment, the semiconductor element 2 is mechanically bonded to the substrate 40. It should be noted that the bonding process can be performed without pressure or with pressure. When pressurized, the adhesion between the conductive paste and the lead frame, the package substrate, etc. is improved.
[0099] Since the conductive connecting member 50 is a metal porous body formed by metal particles (P) in surface contact and bonding (sintering), it has moderate elasticity and softness, and the conductivity is not impaired. The porosity of the metal porous body is 6 to 9% by volume, and the average pore diameter is in the range of 15 to 120 nm. It should be noted that the porosity in the conductive connecting member 50, the average particle size of the metal particles, and the average pore diameter are measured as follows.
[0100] (1) Method for measuring average particle size of metal particles
[0101] The cross-sections of 10 randomly selected particles of the metal particles were observed using a scanning electron microscope (SEM), and the diameter of the largest inscribed circle relative to the two-dimensional shape of the cross-section was measured to obtain the average value. It should be noted that in the cross-sectional photograph of the electron microscope, when the two-dimensional shape is approximately circular, the diameter of the circle is measured, when it is approximately elliptical, the short diameter of the ellipse is measured, when it is approximately square, the length of the side of the square is measured, and when it is approximately rectangular, the length of the short side of the rectangle is measured.
[0102] (2) Method for measuring average pore diameter
[0103] The “average pore diameter” is obtained by observing the cross-sectional shape of 10 to 20 randomly selected pore diameters using a scanning electron microscope (SEM) and measuring the diameters, and the average value thereof is used.
[0104] (3) Method for determining void ratio
[0105] The porosity can be determined by analyzing the cross-sectional image of an electron microscope photograph taken with a transmission electron microscope (TEM). In addition, the porosity when the pore size is less than 100 nm is determined by thinning the sample with an ultramicrotome and observing it with a transmission electron microscope (TEM).
[0106] Afterwards, if Figure 6 As shown, a wire bonding process is performed to electrically connect the front end of the terminal portion (not shown) of the substrate 40 to the electrode pad (not shown) on the semiconductor element 2 using a bonding wire 60. As the bonding wire 60, for example, a gold wire, an aluminum wire or a copper wire is used. The temperature during wire bonding is preferably above 80°C, more preferably above 120°C, and the temperature is preferably below 250°C, more preferably below 175°C. In addition, the heating time is several seconds to several minutes (for example, 1 second to 1 minute). The wiring is performed by heating in a manner to reach the temperature range and using vibration energy based on ultrasonic waves and crimping energy based on applying pressure.
[0107] Next, a sealing step is performed to seal the semiconductor element 2 with a sealing resin 70. This step is performed to protect the semiconductor element 2 and the bonding wire 60 mounted on the substrate 40. This step is performed by molding the sealing resin with a mold. As the sealing resin 70, for example, an epoxy resin is used. The heating temperature during resin sealing is preferably 165°C or more, more preferably 170°C or more, and the heating temperature is preferably 185°C or less, more preferably 180°C or less.
[0108] If necessary, the sealant may be further heated (post-curing step). In this way, the sealing resin 70 that is insufficiently cured in the sealing step can be completely cured. The heating temperature can be set appropriately. In this way, the semiconductor device 100 can be manufactured.
[0109] It should be noted that, in the above example, a bonding film is used when bonding the back side of the semiconductor element 2 where no circuit is formed to the substrate 40; however, this is not limited to this, and a bonding film may also be used when bonding the surface of the semiconductor element 2 where a circuit is formed to the substrate 40 (so-called flip chip mounting).
[0110] Example
[0111] Hereinafter, examples of the present invention will be described; however, the present invention is not limited to these examples.
[0112] (i) Preparation of Copper Particles and Copper Particle Slurry
[0113] A conductive slurry is prepared by kneading 70% by mass of copper particles and 30% by mass of an organic dispersion medium, wherein the copper particles are prepared in an aqueous solution by electroless reduction from copper ions and have an average primary particle size of 150 nm, and the organic dispersion medium comprises 95% by mass of a mixed solvent (equivalent to an organic solvent (S1)) and 5% by mass of ethyl cellulose (average molecular weight 1000000) as an organic binder, and the mixed solvent is composed of 40% by volume of glycerol as an organic solvent, 55% by volume of N-methylacetamide, and 5% by volume of triethylamine.
[0114] (ii) Preparation of Silver Particles and Silver Particle Slurry
[0115] A conductive paste was prepared by kneading 70% by mass of silver fine particles having an average primary particle size of 100 nm (manufactured by Sigma Aldrich Japan Co., Ltd., model number: 730777) and 30% by mass of an organic dispersion medium, wherein the organic dispersion medium contained 95% by mass of a mixed solvent (corresponding to the organic solvent (S1)) and 5% by mass of ethyl cellulose (average molecular weight 1000000) as an organic binder, wherein the mixed solvent consisted of 40% by volume of glycerol as an organic solvent, 55% by volume of N-methylacetamide, and 5% by volume of triethylamine.
[0116] On the mounting table, a release film (50 μm polyethylene terephthalate film) was placed, and a SUS spacer with a thickness of 350 μm and a circular opening of 6 inches in the center was placed on it. On the release film facing the opening of the spacer, 5.0 g of the above-mentioned conductive paste was placed, and the conductive paste was screen-printed and rolled using a scraper to form a circular sheet. Then, after removing the spacer, pre-drying was performed at 110° C. for 15 minutes in an inert atmosphere to produce a conductive bonding layer.
[0117] Separately, 90% by mass of methanol was mixed with 10% by mass of polyglycerol to dilute the polyglycerol, thereby preparing an adhesive layer composition.
[0118] Then, the adhesive layer composition was applied by spray coating on the conductive bonding layer on a hot plate heated to 50° C. so that the film thickness after drying was 2 μm, and dried at 50° C. for 180 seconds to form an adhesive layer. In this manner, a bonding film was obtained.
[0119] On the other hand, an adhesive film was prepared as follows. 65 parts by weight of butyl acrylate, 25 parts by weight of 2-hydroxyethyl acrylate, and 10 parts by weight of acrylic acid were subjected to free radical polymerization, 2-isocyanatoethyl methacrylate was added dropwise and reacted, and 3 parts by weight of polyisocyanate as a curing agent and 1 part by weight of 1-hydroxy-cyclohexyl-phenyl-ketone as a photopolymerization initiator were added to the synthesized acrylic copolymer with a weight average molecular weight of 800,000 and mixed to prepare an adhesive layer composition. The prepared adhesive layer composition was applied to a film (a coating film other than the substrate film) in such a manner that the dry film thickness was 10 μm, and dried at 120°C for 3 minutes. Thereafter, the adhesive layer composition applied to the film was transferred to a 100 μm thick polypropylene-elastomer (PP: HSBR = 80:20 elastomer) resin film as the substrate film, thereby preparing an adhesive film.
[0120] In addition, Novatech FG4 manufactured by Nippon Polychem Co., Ltd. was used as polypropylene (PP), and DYNARON 1320P manufactured by JSR Co., Ltd. was used as hydrogenated styrene butadiene (HSBR). A silicone release-treated PET film (Teijin: Hyprelex S-314, thickness 25 μm) was used as the coating film.
[0121] Thereafter, the conductive bonding layer of the bonding film was bonded onto the adhesive layer of the adhesive film to obtain a wafer processing tape according to the example.
[0122] As a semiconductor wafer, a wafer with a chip electrode layer of Ti / Au=100nm / 200nm formed on the surface of a semiconductor wafer with a thickness of 230μm was prepared, and as a substrate, a semi-hard oxygen-free copper plate with a thickness of 1.2mm was prepared. The wafer processing tape of the above-mentioned embodiment was placed on a hot plate heated to 80°C for heating, and the surface of the semiconductor wafer was adhered to the adhesive layer in a state where the adhesion between the adhesive layer and the surface of the semiconductor wafer (the surface on the chip electrode layer side) was improved, and then the temperature was restored to room temperature. In a state where the adhesive layer was cooled and solidified, a cutting device (DAD340 (trade name) manufactured by DISCO) was used to cut it into 7mm×7mm semiconductor chips together with the bonding film. Thereafter, a high-pressure mercury lamp ultraviolet irradiator was used to irradiate from the substrate film side of the adhesive film so that the irradiation amount was 200mJ / cm 2 Then, the adhesive film was expanded using a chip bonder (Canon Machinery Co., Ltd., CPS-6820 (trade name)), and the semiconductor chip was picked up together with the bonding film in this state, and the conductive bonding layer side of the bonding film was placed on the substrate.
[0123] Subsequently, for the stack of the above-mentioned semiconductor chip, bonding film, and substrate, the conductive bonding layer formed by the copper particle paste was heated at 300°C for 60 minutes, and the conductive bonding layer formed by the silver particle paste was heated at 250°C for 60 minutes to sinter the conductive bonding layer, thereby producing 20 mounted samples.
[0124] The mounted samples were subjected to a thermal shock test with one cycle of keeping at -55°C for 30 minutes and at 200°C for 30 minutes. The samples were taken out every 100 times and visually inspected for cracks and peeling. Afterwards, ultrasonic waves were irradiated from the semiconductor chip side using an ultrasonic microscope (Mi-Scope (trade name) manufactured by Hitachi Construction Machinery Co., Ltd.) and a probe (model "PQ2-13", 50 MHz), and peeling was measured using a reflection method. Mounted samples with a peeling area greater than 10% were judged to be faulty. For the mounted samples using the bonding film of the wafer processing tape of this embodiment, whether it was formed of copper particles or silver particles, the number of TCTs until it was judged to be a fault was more than 1000 times, which is a result of high reliability.
[0125] Furthermore, by using the wafer processing tape of this embodiment, the semiconductor wafer and the bonding film can be cut at the same time, and the cut semiconductor chip can be picked up together with the bonding film and placed on the substrate, so the mounting process can be performed simply.
[0126] Explanation of symbols
[0127] 2 semiconductor element, 10 wafer processing tape, 11 release film, 12 adhesive film, 12a base film, 12b adhesive layer, 13 bonding film, 13a conductive bonding layer, 13b adhesive layer, 40 substrate.
Claims
1. A laminated body, characterized in that: An adhesive film having a base film and an adhesive layer provided on the base film, The bonding film used to bond the semiconductor element to the substrate and the semiconductor wafer are bonded together. The bonding film comprises: A conductive bonding layer obtained by forming a conductive paste containing metal fine particles P into a film shape, and an adhesive layer having adhesiveness and stacked on the conductive bonding layer, The average primary particle size of the metal particles P is 10 nm to 500 nm. The conductive bonding layer is attached to the adhesive layer, and the semiconductor wafer is attached to the adhesive layer. The adhesive layer is thermally decomposable and contains a substance that reduces the metal particles P. The adhesive layer is thermally decomposed by heating during bonding, and the metal particles P of the conductive bonding layer are sintered, thereby bonding the semiconductor element to the substrate. The adhesive layer contains one or more selected from polyglycerol, glycerol fatty acid ester, polyglycerol fatty acid ester, phosphines, phosphites, sulfides and sulfoxides, or contains one or more selected from disulfides and trisulfides.
2. The laminate according to claim 1, characterized in that: The semiconductor wafer and the bonding film are cut into individual semiconductor element units.
3. The laminate according to claim 1 or 2, characterized in that: The conductive paste includes an organic solvent S.
4. The laminate according to claim 1 or 2, characterized in that: The metal particles P are composed of copper or silver.
5. The laminate according to claim 1 or 2, characterized in that: The conductive paste includes an organic binder R.
6. The laminate according to claim 1, wherein: The sulfides include one or more selected from bis(4-methacryloylthiophenyl) sulfide, phenyl-p-tolyl sulfide, and furfuryl sulfide.
7. The laminate according to claim 3, characterized in that: The organic solvent S contains an organic solvent SC having a boiling point of 100° C. or higher under normal pressure and composed of an alcohol having one hydroxyl group in the molecule and / or a polyol having two or more hydroxyl groups in the molecule.
8. The laminate according to claim 5, characterized in that: The organic binder R is one or more selected from cellulose resin binders, acetate resin binders, acrylic resin binders, urethane resin binders, polyvinyl pyrrolidone resin binders, polyamide resin binders, butyral resin binders and terpene binders.
Citation Information
Patent Citations
Semiconductor device and its manufacturing method
JP2006352080A
Method of manufacturing copper fine particle
JP2008231564A
Adhesive film and tape for wafer processing
JP2010265453A
Connection sheet
JP2013236090A
Conductive connecting member and manufacturing method of same
CN102812543A